OPERATIONAL EFFICIENCY ASSESSMENT OF URBAN PEDESTRIAN INFRASTRUCTURE: QUEUEING SYSTEM ANALYSIS OF ATAL FOOTBRIDGE - Patel, Anjali; Gor, Ravi (International Journal of Engineering Science Technologies, 2025)
This study focuses on analyzing the queueing system at the Atal Bridge, Ahmedabad to understand and improve its operational efficiency. The bridge's functioning is divided into two main parts: the ticket window and the bridge visit. Primary data, including arrival rates and service times, were collected through direct observation. The collected data was analyzed to determine its distribution, which was used to construct a suitable queueing model. Using this queueing model, a numerical analysis was performed to identify the causes of crowding and delays in the system. Moreover, the performance measures of weekdays (Monday to Friday) and weekends (Saturday and Sunday) were compared in the analysis to highlight differences in crowd patterns and system efficiency. The results of this analysis provide valuable insights into how the system can be improved to reduce waiting times and enhance the overall visitor experience. This research highlights the practical application of queueing theory in managing pedestrian flow and improving the efficiency of public infrastructure like the Atal Bridge.